Pore structure and strength of waste fiber recycled concrete. (September 2019) - Zhou, Jinghai; Kang, Tianbei; Wang, Fengchi
The pore structure is one of the major factors affecting the mechanical properties of waste fiber recycled concrete. In this article, the pore structure and strength performance of waste fiber recycled concrete are experimentally studied. The design variables are water–cement ratio, recycled aggregate replacement rate, waste fiber length, and volume fraction of waste fibers. The pore structure characteristic parameters of waste fiber recycled concrete are investigated using mercury intrusion porosimetry test and fractal theory. The complex distribution of pore structure in space is quantitatively described by fractal dimension, and the pore structure is comprehensively evaluated. The results show that the water–cement ratio has the largest influence on the pore structure, and the fiber length has the least influence. The optimum volume fraction of waste fibers is 0.12%. There is an obvious linear relationship between the pore volume fractal dimension and strength. With the increase in the fractal dimensions, the compressive and splitting tensile strengths increase. Macroscopic mechanical properties of waste fiber recycled concrete can be predicted by the pore structure.